2009
DOI: 10.2164/jandrol.108.005843
|View full text |Cite
|
Sign up to set email alerts
|

Length of Androgen Receptor—CAG Repeats in Fertile and Infertile Egyptian Men

Abstract: Androgens play key roles in spermatogenesis, and they exert their effect via the androgen receptor (AR). The AR gene has a repetitive DNA sequence in exon 1 that encodes a polyglutamine tract. Instability in the glutamine (CAG) repeat unit length is polymorphic across ethnic groups. Previous studies of the relationship between the repeat unit length and male infertility have been contradictory. To establish the range of wild-type alleles in Egyptian men, we determined the range of repeat lengths in a populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 66 publications
6
25
0
Order By: Relevance
“…These results were consistent with other studies in which no association was found (Dadze et al, 2000;Sasagawa et al, 2001;Van Golde et al, 2002;Rajpert-De Meyts et al, 2002;Lund et al, 2003;Martinez-Garza et al, 2008;Badran et al, 2009), but discordant with other studies that did find associations (Tut et al, 1997;Komori et al, 1999;Dowsing et al, 1999;Yoshida et al, 1999;Mifsud et al, 2001;Patrizio et al, 2001;Wallerand et al, 2001;Mengual et al, 2003;Katagiri et al, 2006). However, for CAG repeats >23, risks of >1.2-fold and >1.8-fold were found in azoospermia and severe oligospermia compared to the controls, although CAG repeat length was not significantly correlated with sperm counts in azoospermia and severe oligospermia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were consistent with other studies in which no association was found (Dadze et al, 2000;Sasagawa et al, 2001;Van Golde et al, 2002;Rajpert-De Meyts et al, 2002;Lund et al, 2003;Martinez-Garza et al, 2008;Badran et al, 2009), but discordant with other studies that did find associations (Tut et al, 1997;Komori et al, 1999;Dowsing et al, 1999;Yoshida et al, 1999;Mifsud et al, 2001;Patrizio et al, 2001;Wallerand et al, 2001;Mengual et al, 2003;Katagiri et al, 2006). However, for CAG repeats >23, risks of >1.2-fold and >1.8-fold were found in azoospermia and severe oligospermia compared to the controls, although CAG repeat length was not significantly correlated with sperm counts in azoospermia and severe oligospermia.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies on CAG repeats in infertile men have reported conflicting results. Some suggested no expansion (Dadze et al, 2000;Sasagawa et al, 2001;Van Golde et al, 2002;Rajpert-De Meyts et al, 2002;Lund et al, 2003;MartinezGarza et al, 2008;Badran et al, 2009), while others reported increased length (but still within the normal range) with respect to controls (Tut et al, 1997;Dowsing et al, 1999;Yoshida et al, 1999;Mifsud et al, 2001;Patrizio et al, 2001;Wallerand et al, 2001;Mengual et al, 2003;Katagiri et al, 2006). Only one study indicated that reduced CAG repeats are closely associated with impaired spermatogenesis in infertile men (Komori et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The AR uniquely contains an extended N-terminal domain which includes polymorphic polyglutamine (CAG) and poly-glycine (GGN) repeats which are known to influence AR activity [2,3]. In clinical studies, the CAG repeat length has an association with genital abnormalities [3], a positive correlation with serum testosterone concentrations but not with male infertility [4]. A shorter CAG repeat polymorphism may increase the risk of prostate cancer [5].…”
Section: Molecular Aspects Of the Androgen Receptormentioning
confidence: 99%
“…Current studies investigating the correlation between CAG length, fertility and impaired sperm production do (Tut et al 1997;Dowsing et al 1999;Mifsud et al 2001;von Eckardstein et al 2001;Claessens et al 2005) or do not (Dadze et al 2000;Rajpert-De Meyts et al 2002;Westerveld et al 2008;Badran et al 2009) find a connection. Davis-Dao et al (2007) identified a mild association of AR-CAG length on male idiopathic infertility by comparing 33 reports in a meta-analysis.…”
Section: Introductionmentioning
confidence: 98%